Pedagogical bridges to heritage: teacher attitudes and practices in heritage language maintenance - Kosan, Y; Akgul, E; Elmas, R (International Journal Of Multilingualism)
This study examines the perspectives of teachers in Djibouti, Ethiopia, and Cameroon on maintaining students' heritage languages and how these attitudes are reflected in classroom practices. The research highlights teachers' attitudes toward heritage languages maintenance and their impact on cultural and cognitive development. The study utilised a mixed-methods approach and involved a diverse cohort of 358 teachers from Djibouti, Ethiopia, and Cameroon, encompassing various demographic characteristics in three countries. Data were gathered via the Teachers' Attitudes Towards Students' Heritage Language Maintenance Survey, which included 35 Likert-type items and three open-ended interview questions. Quantitative findings indicate that demographic factors such as professional experience and language proficiency do not significantly impact teachers' attitudes toward heritage language maintenance. Qualitative data reveal that teachers emphasise cultural maintenance and cognitive development as reasons for supporting heritage language maintenance. Significant barriers identified include educational challenges and social integration issues. The research underscores the critical role of collaboration between teachers and parents in sustaining heritage languages. These findings indicate that academic policies and teacher-parent partnerships could play a role as important as individual teacher characteristics in encouraging educational institutions to develop more inclusive policies, promote linguistic diversity, and build effective partnerships to create more inclusive educational environments.
Keywords: Heritage language maintenance; teacher attitudes; classroom practices